The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.35840/2631-5076/9265
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Dissimilar Friction Welded SAF 2205 Duplex Stainless Steel and 1045 Medium Carbon Steel Joints

Abstract: This study investigated the microstructure and mechanical properties of frictional welded joints between SAF 2205 duplex stainless steel and AISI 1045 medium carbon steel. The welded joints were fabricated by varying the friction pressure, friction time, and keeping the forging pressure, forging time and rotational speed as constant to obtain a constant range of welding temperature (780-800 °C). The results revealed that as the friction pressure increases and friction time decreases, weld interface hardness va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…After that, the friction time influence was discovered by an experimental study by Serkan et al [19], where they found that raising the friction time resulted in a significant increase in hardness. The forging pressure parameter effect on mechanical properties was investigated by Gawhar et al [20]. They found that the hardness values and the welding strength increased with increasing the forging pressure.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the friction time influence was discovered by an experimental study by Serkan et al [19], where they found that raising the friction time resulted in a significant increase in hardness. The forging pressure parameter effect on mechanical properties was investigated by Gawhar et al [20]. They found that the hardness values and the welding strength increased with increasing the forging pressure.…”
Section: Introductionmentioning
confidence: 99%